The Asteraceae family in the state of Nayarit (Mexico) - Ortiz-Bermudez, Enrique; Villaseñor, Jose Luis; Tellez, Oswaldo (Instituto de Ecología, A.C., 1998)
The state of Nayarit occupies a strategic position in Mexico; it encompasses the vertex of three important mountain ranges (Eje Volcánico Transversal, Sierra Madre Occidental and Sierra Madre del Sur); this largely determines its high floristic diversity. In the state, Asteraceae is the most diverse family of flowering plants, with 122 genera and 447 species. This paper includes an updated list of species of Asteraceae found in Nayarit and this diversity is compared to that found in the neighbouring states. A list of the endemic species to Nayarit is also included.